Utilization of Audio Visual Media as a Source History Learning - Ainina, Indah Ayu (Indonesian Journal of History Education, 2018)
The research problem is centered on applying audiovisual media in teaching history, specifically within the history learning class of XI students at High School 2 Holy Bae during the academic year 2013/2014. This investigation seeks to explore whether the utilization of audiovisual media in teaching history has a significant impact on the learning outcomes of these students. The study aims to assess the effectiveness of audiovisual media in enhancing the student's understanding and retention of historical knowledge. Furthermore, it intends to measure how much audiovisual media influences the overall learning outcomes of class XI students at High School 2 Holy Bae during the 2013/2014 academic year. The study will provide insights into the benefits and challenges of integrating audiovisual media into history education by focusing on these objectives. Additionally, the research will offer educators recommendations on effectively incorporating such media to improve student engagement and academic performance. The primary goals of this study are to evaluate the use of audiovisual media-based teaching methods in history education, to determine the learning outcomes of class XI students, and to analyze the impact of audiovisual media on the academic achievements in the history subjects of class XI Social at High School 2 Bae Kudus. This comprehensive investigation aims to contribute to the broader field of educational media and its application in enhancing history education's teaching and learning processes.